(untitled) (Journal of Rangpur Medical College, 2024)
Background: Food contamination can occur in any step of handling of food from “farm to table” and lead to a variety of food borne diseases which can cause increased morbidity and mortality. Food handlers play a vital role in transmitting these diseases and pose a significant threat to public health. Objective: This study was aimed to assess knowledge about food safety and handling practices of adult rural women who were actively involved with food preparation. Methods: A cross-sectional descriptive study was conducted among 664 adult rural women involved with food preparation of households in six villages of Taraganj Upazila, Rangpur district from 20th September 2023 to 19th October 2023. Pre-tested semi-structured questionnaire was used to collect data and face-to-face interview with the respondents were performed. Results: About 46.1% participants were between the age group of 18-34 years (Mean±SD=36.07±11.6 years). 58.9% educational status was below SSC.43.2% respondents had monthly family income between (10,001-20,000) taka. 95.2%of the respondents did not attend any type of food safety training or session. Among all 47.0% had good knowledge and only 13.4% had good handling practice. 98.8% respondents knew about hand washing before food preparation but only 78.3% practiced it. About 81.5% of respondents knew that keeping raw fish/meat/vegetable in same bag/vessels is harmful to health, but during practice 70.6% participants reported that they always used separate utensils for raw and cooked food during food preparation. 93.8% knew that raw fish, meat, and eggs should be completely cooked, and food should be served piping-hot, although 41% of them always practiced thorough cooking and re-heating cooked foods until it is piping-hot. 89.5% of respondents knew that expiry date of packed/canned food should be checked before eating/cooking but 66.6% always threw away expired foods. 98.9% of the respondents said that it is mandatory to wash raw fruits and vegetables with safe water before cooking/eating but 84.6% of thempractice this. 81.2% knew that diarrhea/skin disease of cook can contaminate food, 70.9% of them avoid servingfood while they are infected with these diseases. The association between food handling practice and food safety knowledge was strongly significant (p<.001) Conclusion: The findings of this study portray the importance of education and awareness and training orcourtyard session about safe food handling knowledge for prevention of food borne illness todecrease mortality and morbidity from these diseases. J Rang Med Col. September 2024; Vol. 9, No. 2: 15-20